Bacterial Acute Otitis Media Complicated with Otorrhea in a Children’s Hospital in the Era of Pneumococcal Conjugate Vaccines - Irene Tzovara; Anastasios Doudoulakakis; Georgios Kalogeras; Emmanouil Koutouzis; Charilaos Dellis; Sophia Pasparakis; Marietta Charakida; Evangelia Lebessi; Elisavet Bozavoutoglou; Michael Tsakanikos; Vassiliki Syriopoulou; Maria Tsolia (Pathogens)
Acute otitis media (AOM) is a common disease among children and can be complicated by otorrhea (AOMO). In 2010, the 13-valent Pneumococcal Conjugate Vaccine (PCV13) replaced the 7-valent vaccine (PCV7) in Greece. We aimed to describe the microbiological profile of bacterial ΑOMO among children younger than 16 years across the two PCV periods in a tertiary children’s hospital. Middle ear fluid cultures from 2418 children with AOMO were collected from 2007 to 2022. Otopathogens were isolated and tested for antimicrobial susceptibility. Data were compared between the PCV7- (2007–2011) and PCV13-period (2012–2019). The most common otopathogen over the 16-year period was S. pyogenes (35.4%), followed by H. influenzae (33.8%), S. pneumoniae (26.6%), and M. catarrhalis (4.1%). Pneumococcal resistance to cefotaxime and clindamycin significantly increased from 2% to 4.5% (p = 0.019) and 16.1% to 22.8% (p = 0.039), respectively. Resistance of H. influenzae to ampicillin increased from 6.3% to 13.9% (p < 0.001). A significant reduction in cotrimoxazole-resistant S. pneumoniae from 31% to 22.4% (p = 0.012), and in clindamycin-resistant and erythromycin-resistant S pyogenes, from 17.4% to 9.3% and 21.4% to 10.8%, respectively (p ≤ 0.001), was observed. During 2013–2022, 38 S. pneumoniae serotypes were identified among 250 isolates. Serotype 3 (27.2%) and 19A (13.2%) prevailed, followed by 19F (7%). The most common causes after the shift to PCV13 are S. pyogenes and H. influenzae. However, S. pneumoniae remains an important otopathogen with significant antimicrobial resistance. Serotype 3 was mostly detected, followed by 19A.